Huma Betang Sebagai Wadah Merajut Kebhinekaan di Kalimantan Tengah - sutarwan, sutarwan (Fakultas Dharma Duta, 2023)
Huma betang is a traditional house from Central Kalimantan. Huma betang means long house or big house. Huma betang resembles a stilt house which, when viewed from the model and construction of the building, is tall and elongated and consists of many rooms that can be occupied by ten to forty heads of household. The values of diversity contained in huma betang are the values of tolerance, the values of mutual cooperation, the values of harmony, and the values of justice. So that huma betang can be said as a place to knit diversity in Central Kalimantan. The method used in this research is the literature study method.